1991
DOI: 10.1254/jjp.57.63
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cimetidine on Adaptive Cytoprotection by Mild Irritant Dose of HC1 in the Rat Gastric Mucosa

Abstract: ABSTRACT--While cimetidine (CIM) is strikingly effective in inhibiting gastric acid secretion, its effect on the defensive mechanisms of the gastric mucosa has been con troversial. The aims of the present study were to test if administration of CIM at an antisecretory dose is protective against acid-induced injury and to assess its effect on adaptive cytoprotection induced by non-necrotizing concentrations of HCl in rats. A dose of 100 mg/kg of CIM was administered once, or twice a day for 5 days intraperi ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[37] have shown that certain prostaglandins maintain the cellular integrity of the gastric mucosa by a mechanism other than the inhibition of gastric acid secretion. On the other hand, inhibition of gastric acid secretion failed to offer cytoprotection of gastric mucosa against necrotizing agents [38,39]. Thus, the antisecretory compounds may or may not be cytoprotective, depending on the type and severity of gastric lesions [40–42].…”
Section: Discussionmentioning
confidence: 99%
“…[37] have shown that certain prostaglandins maintain the cellular integrity of the gastric mucosa by a mechanism other than the inhibition of gastric acid secretion. On the other hand, inhibition of gastric acid secretion failed to offer cytoprotection of gastric mucosa against necrotizing agents [38,39]. Thus, the antisecretory compounds may or may not be cytoprotective, depending on the type and severity of gastric lesions [40–42].…”
Section: Discussionmentioning
confidence: 99%